The Black Angels : the untold story of the nurses who helped cure tuberculosis. - Smilios, Maria (G. P. Putnam's Sons, 2023)
"During those dark pre-antibiotic days, when tuberculosis killed one in seven people, white nurses at Sea View, New York's largest municipal hospital, began quitting. Desperate to avert a public health crisis, city officials summoned Black southern nurses, luring them with promises of good pay, a career, and an escape from the strictures of Jim Crow. But after arriving, they found themselves on an isolated hilltop in the remote borough of Staten Island, yet again confronting racism and consigned to a woefully understaffed facility, dubbed "the pest house" where "no one left alive." Spanning the Great Depression and moving through World War II and beyond, this story follows the intrepid young women, the "Black Angels," who, for twenty years, risked their lives working under dreadful conditions while caring for the city's poorest--1,800 souls languishing in wards, waiting to die or become "guinea pigs" for experimental (often deadly) drugs. Yet despite their major role in desegregating the NYC hospital system--and regardless of their vital work in helping to find the cure for tuberculosis at Sea View-these nurses were completely erased from history. The Black Angels recovers the voices of these extraordinary women and puts them at the center of this riveting story celebrating their legacy and spirit of survival"--